2004
DOI: 10.1080/13854040490501574
|View full text |Cite
|
Sign up to set email alerts
|

A Status Report On the Practice of Forensic Neuropsychology

Abstract: The practice of forensic neuropsychology has experienced tremendous growth over the past two decades, becoming perhaps the most rapidly expanding area of practice within the field of clinical neuropsychology. Indeed, there have been many important advancements in the field that have helped to position neuropsychologists as instrumental participants within the forensic arena. Yet, there is currently no consensus in our field regarding what constitutes competency in forensic neuropsychology and also no specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…Specifically, whereas the growth of forensic neuropsychology can be readily seen in the clinical and academic interests of neuropsychologists, Heilbronner (2004) noted that the subspecialty is currentiy limited by its lack of dedicated professional organizations, practice standards (or less formal practice guidehnes), and specialized certification and credentialing procedures.…”
mentioning
confidence: 98%
“…Specifically, whereas the growth of forensic neuropsychology can be readily seen in the clinical and academic interests of neuropsychologists, Heilbronner (2004) noted that the subspecialty is currentiy limited by its lack of dedicated professional organizations, practice standards (or less formal practice guidehnes), and specialized certification and credentialing procedures.…”
mentioning
confidence: 98%
“…According to Archer et al 47 , this is due to methods of investigation that have won "general acceptance" in the field. In this way, the development of methodological strategies, tools, as well as a series of recommendations that can guide procedures for utilization of neuropsychology in the forensic field follows the studies' expectations for this topic 2,6,11,49,50 .…”
Section: Neuropsychological Assessment For Verification Of Civil Capamentioning
confidence: 99%
“…Although we have identified 12 articles in the category "Descriptions of methods, proceedings, standards, validation of instruments, range and limits of Neuropsychological Assessment in forensic field" just two 2 works discuss standards and conduct of the practice of neuropsychological assessment in order to address legal issues 6,48 .…”
Section: Neuropsychological Assessment For Verification Of Civil Capamentioning
confidence: 99%
See 1 more Smart Citation
“…Michaels (2008) demonstrated that the source of funding for research influences the outcome of that research and how each legal side may use those research findings. In the field of clinical neuropsychology, forensic consultation has become a major factor of practice as well as research (Sweet et al 2006;Heilbronner 2004), yet the field has not attempted to investigate the relationship of funding, practice orientation, participation of retained forensic experts, or other issues that legal retention and funding have had on neuropsychological research findings and publications.…”
mentioning
confidence: 99%